Optimization of Electricity Supply in East Nusa Tenggara Through Communal Solar Power Plants: A Case Study of Kupang City Using PVSyst - Fahmy Rinanda Saputri; Indra Hadi Prasetya; Agie Maliki Akbar (Universitas Islam Raden Rahmat, Malang, 2024)
Certain regions in Indonesia face challenges related to inadequate electricity supply. To address this, it is essential to model and simulate potential solutions before implementation. This study focuses on optimizing electricity provision to resolve a 4 MW deficit in Kupang, East Nusa Tenggara, particularly at night, through the development of a communal Solar Power Plant. PVsyst software is used for analysis to determine the most economical and optimal solar system configuration. The Oelnasi site, selected for its solar radiation levels, land availability, and proximity to the grid, will house 17,411 solar panels covering 28,360 m², with 196 inverters. The system will generate 4.005 kWp of PV power, with a maximum DC power of 3.583 kWDC, and an AC power of 2.940 kWAC. Simulation results indicate that the Oelnasi Solar Power Plant can supply stable nighttime electricity and reduce CO2 emissions by approximately 7,200 tons annually.